Organizační teorie, současný stav a výhled - Buchta, Miroslav (Univerzita Pardubice, 1998)
In this paper certain aspects of the present organization theories for industrial companies are given. In the first part of the paper a choice of organization ideas of famous management "gurus" P. F. Drucker, H. Koontz, H. Weihrich, T. J. Peters and R. H. Waterman are presented. In the second part of the similar conclusions of czech management experts are shown. The third part of this publications brings proposals and recommendations of the author, how to stabilize and improve organization structures. Results of this paper are very valuable and are applicable namely to industrial companies of the Czech Republic.
Keywords: organizační teorie; organizační struktury; Management